Wolbachia Infection Alters Olfactory-Cued Locomotion in Drosophila spp. - Peng, Yu (American Society for Microbiology (ASM), 2008)
Wolbachia pipientis is an endosymbiotic bacterium present in diverse insect species. Although it is well studied for its dramatic effects on host reproductive biology, little is known about its effects on other aspects of host biology, despite its presence in a wide array of host tissues. This study examined the effects of three Wolbachia strains on two different Drosophila species, using a laboratory performance assay for insect locomotion in response to olfactory cues. The results demonstrate that Wolbachia infection can have significant effects on host responsiveness that vary with respect to the Wolbachia strain-host species combination. The wRi strain, native to Drosophila simulans, increases the basal activity level of the host insect as well as its responsiveness to food cues. In contrast, the wMel strain and the virulent wMelPop strain, native to Drosophila melanogaster, cause slight decreases in responsiveness to food cues but do not alter basal activity levels in the host. Surprisingly, the virulent wMelPop strain has very little impact on host responsiveness in D. simulans. This novel strain-host relationship was artificially created previously by transinfection. These findings have implications for understanding the evolution and spread of Wolbachia infections in wild populations and for Wolbachia-based vector-borne disease control strategies currently being developed.